Perceived Barriers Of Knowledge Sharing At Individual, Organisational And Technological Levels: A Case Study On MARDI - Subramaniam, Suthashini (2007)
This project is to explore and identify the common barriers of knowledge sharing in aresearch based organisation. The research based organisation which is selected for this research project purpose is the Malaysian Agricultural Research and Development Institute (MARDI). It was established in 1969. The objective of this project is to explore and identify the knowledge sharing barriers at MARDI, based on three levels, which are individual, organisational and technological levels.